A cluster of HTLV-1 associated tropical spastic paraparesis in Equateur (Zaire): ethnic and familial distribution. Issue 1 (January 1990) - Kayembe, K; Goubau, P; Desmyter, J; Vlietinck, R; Carton, H
Abstract : In Lisala, Equateur province, Zaire, 25 patients from 21 pedigrees were identified with human T-lymphotropic virus type 1 (HTLV-1) associated tropical spastic paraparesis (TSP). In the 10 (48%) pedigrees with additional genuine TSP cases established mainly by history, seven of 10 patients' mothers, no fathers or spouses, one of 59 surviving offspring, five of 105 siblings, and six other close blood relatives had TSP. A child may develop TSP before its mother. Three familial cases were in paternal relatives only. In total, 39 cases (11 men, 28 women) were identified in this population of about 50, 000. Half were in the Mundunga minority of less than or equal to 10% (p less than 0.001). The data suggest maternal transmission of HTLV-1 and enhanced TSP susceptibility in those infected due to familial, probably genetic factors.